No Significant Effects of IL-23 on Initiating and Perpetuating the Axial Spondyloarthritis: The Reasons for the Failure of IL-23 Inhibitors - Zhang, Hua; Jiang, Han-Lei; Dai, Sheng-Ming (Frontiers in Immunology, 2022)
Axial spondyloarthritis (axSpA) is comprised of ankylosing spondylitis (AS) and non-radiographic axSpA. In recent years, the involvement of the IL-23/IL-17 axis in the pathophysiology of axSpA has been widely proposed. Since IL-23 is an upstream activating cytokine of IL-17, theoretically targeting IL-23 should be effective in axSpA, especially after the success of the treatment with IL-17 blockers in the disorder. Unfortunately, IL-23 blockade did not show meaningful efficacy in clinical trials of AS. In this review, we analyzed the possible causes of the failure of IL-23 blockers in AS: 1) the available data from an animal model is not able to support that IL-23 is involved in pre-clinical rather than clinical phase of axSpA; 2) Th17 cells are not principal inflammatory cells in the pathogenesis of axSpA; 3) IL-17 may be produced independently of IL-23 in several immune cell types other than Th17 cells in axSpA; 4) No solid evidence supports IL-23 is a pathogenic factor to induce enthesitis and bone formation. Taken together, IL-23 is not a principal proinflammatory cytokine in the pathogenesis of axSpA.